Effect of Trabeculotomy on Corneal Endothelial Cell Loss in Cases of After Penetrating-Keratoplasty Glaucoma. Issue 3 (March 2017) - Kusakabe, Ayaka; Okumura, Naoki; Wakimasu, Koichi; Kayukawa, Kanae; Kondo, Masami; Koizumi, Noriko; Sotozono, Chie; Kinoshita, Shigeru; Mori, Kazuhiko
Abstract : Purpose: The aim of this study was to evaluate the effect of trabeculotomy (TLO) on glaucoma and endothelial cell loss after penetrating keratoplasty (PK). Methods: A retrospective study was conducted on consecutive patients who underwent PK and in whom more than 24 months of follow-up was available. Patients were categorized into the PK+TLO group [ie, TLO for post-PK glaucoma (n = 10)] and the PK group [PK alone (n = 73)]. Intraocular pressure (IOP) was evaluated during each follow-up examination. Central corneal endothelium images were obtained and analyzed to determine corneal endothelial cell (CEC) density. Results: The mean duration period from original PK to TLO for secondary glaucoma was 25.5 ± 34.9 months in the PK+TLO group. Mean preoperative IOP in the PK+TLO group was 35.8 mm Hg, and decreased to 17.5 mm Hg at 24 months postoperative ( P < 0.01). CEC density decreased in the same manner in both groups. In the PK+TLO group, mean CEC density was 1838 cells per square millimeter before TLO and decreased to 1195 cells per square millimeter at 24 months after TLO. In the PK group, mean CEC density decreased from 1870 to 1209 cells per square millimeter at each corresponding time point. Conclusions: TLO for post-PK glaucoma appeared to safely lower IOP, although repeated surgeries were required in some patients, and did not accelerate CEC loss. Abstract : Supplemental Digital Content is Available in the Text.